Production quality and human factors engineering: A systematic review and theoretical framework. (November 2018) - Kolus, Ahmet; Wells, Richard; Neumann, Patrick
Abstract: The purpose of this paper is to systematically examine available empirical evidence on the impact of human factors (HF) in the design and management of manufacturing operations on system quality performance. A systematic review was conducted to map the linkages between the human-system fit in the design of operations systems (OS) with production quality. A total of 73 empirical studies were identified linking HF to OS performance in manufacturing. Quality risk factors included HF aspects in product design, process design and workstation design of the manufacturing OS. Quality deficits were associated with undesirable human effects of workload like fatigue and injury-related risk factors. Forty-six percent of the studies reported on efforts to improve HF in the OS with effect sizes for quality improvements reaching up to 86%. The paper documents available quality risk factors in the design of OS. It also provides a conceptual framework explaining HF-Quality linkage. Highlights: Better (or worse) human factors in system design yields better (or worse) production quality. Quality risk factors include HF aspects in product design, process design and workstation design of manufacturing operations. Undesirable human effects of workload like fatigue and injury-related risk factors results in quality deficits.